Frontispiece: Single Platinum Atom Doping to Silver Clusters Enables Near‐Infrared‐to‐Blue Photon Upconversion. Issue 6 (1st February 2021) - Niihori, Yoshiki; Wada, Yuki; Mitsui, Masaaki
Abstract : Cluster Compounds In their Communication on page 2822, Masaaki Mitsui et al. report on Pt‐doped Ag clusters as a new NIR‐absorbing sensitizer for photon upconversion. Pt doping significantly increases the intersystem crossing yield of the cluster.